Bird ecological status of two internationally important wetlands 'Ramsar sites and IBA' in Algeria. (31st October 2019) - Bezzalla, Adel; Houhamdi, Moussa; Chenchouni, Haroun
Abstract: This study characterized the ecological status of birds at two Ramsar sites in northeastern Algeria, Chott Tinsilt (TNS) and Sebkhet Ezzemoul (EZZ). During the period 2015–2017, bird counting revealed that bird community was composed of 29 species and 11 families at TNS and 23 species and 10 families at EZZ. Bird species encountered across different habitats were classified into three ecological groups (waterbirds, open habitat birds and mountain birds). Besides, four ecological statuses (phenological status, faunal types, trophic status, and protection categories) were assigned to each species. Birds of both study wetlands have a biogeographical affinity with the faunal type 'Palearctic' (24.1% of species at TNS and 17.4% at EZZ). The Multiple factor analysis of ecological statuses crisscrossed with bird groups indicated that waterbirds are distinguished from other ecological groups because they are predominantly migrants (69.0% of species at TNS and 69.6% at EZZ) that use these two wetlands as wintering ground and migratory staging. Waterbirds included mostly invertebrate feeders, polyphagouss and piscivorous species. Mountain birds were distinguished as unique group because of species trophic status (especially carnivores and scavengers), their phenology (summer migrant breeders), and the abundance of certain protection categories. Open habitats birds were clustered as a separate because of the biogeographic faunal types. Our findings emphasized the importance of using ecological attributes of bird species in a multiple factor analysis to highlight information on the true status of birdlife. This survey characterized the diversity and ecological characteristics of birds of two Ramsar sites, which represent a true natural heritage of proven ecological and socio-economic importance at regional and national scales. Graphical abstract: Image 1 Highlights: Ecological statuses of birds at two IBA and Ramsar sites in NE Algeria were characterized. Biogeographically, birds have affinities towards the Palearctic and Afrotropical faunal types. Waterbirds are winter migrant, mostly invertebrate feeders, polyphages and piscivores. Bird trophic, phenology and protection statuses distinguished mountain birds as unique group. Multiple combinations of bird ecological attributes are important to highlight actual status of birdlife.